SUSTAINABLE DEVELOPMENT OF REGIONS AND EFFECTIVE USE OF NATURAL RESOURCES IN THE CONTEXT OF GLOBAL CLIMATE CHANGE - Khojanova, Gulshoda Otamurodovna (THE INNOVATION ECONOMY, 2026)
This article provides an in-depth scientific analysis of the impact of global climate change on sustainable regional development and the efficient use of natural resource potential. It substantiates the need to revise development strategies due to climate-driven transformations of physical-geographical, agro-economic, hydrological and ecological factors. The paper proposes evidence-based measures for environmentally safe and resource-efficient use of natural resources, the transition to a green economy, and the adoption of innovative mechanisms for water and land governance.